RIBA VS ZAKAT DALAM PERPEKTIF EKONOMI ISLAM - Iwan Ramadhan Sitorus (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2019)
The main characteristic of Islamic economics compared to the conventional economy is the prohibition on taking usury or interest in each transaction. The use of other people's assets in an unfair way, in the form and through any means, is prohibited in the Qur'an. Usury which is interpreted as an addition, definitively involves consuming (eating) the wealth of others in a physical way. Usury is directly opposite the cooperative spirit in Islamic teachings. People who are rich, in Islamic teachings, are required to give the rights of the poor by paying zakat and then giving alms in addition to the zakat. Islam does not allow Muslims to make their wealth a vehicle for sucking the blood of poor people. Al-Qur'an letter Ali Imran verse 130 states that happiness (falah) will be obtained by abandoning this usury system, and at the same time the Qur'an states that happiness cannot be obtained through ribawi practice. Because usury is based on injustice